The Influence of Human Resource Competence, the Implementation of the Regional Financial Accounting System, and the Use of Information Technology on the Quality of Regional Financial Statements at the Bengkalis Regency SKPD - Irma Rahmadani; Fachroh Fiddin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research examines the effect of human resource competence, the implementation of the regional financial accounting system, and the utilization of information technology on the quality of regional financial statements within the Regional Apparatus Work Units (SKPD) of Bengkalis Regency. The study adopts a quantitative research design using primary data collected through questionnaires. The population consists of 90 respondents selected using purposive sampling, with data measured on a Likert scale. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 29. The findings indicate that, individually, human resource competence has a positive and significant effect on the quality of regional financial statements. Likewise, the implementation of the regional financial accounting system and the utilization of information technology also demonstrate positive and significant influences on the quality of financial reporting. The results further show that the adjusted R-squared value reaches 68.1%, suggesting that the quality of regional financial statements is largely explained by the variables examined in this study, while the remaining 31.9% is influenced by other factors beyond the research model.